2013
DOI: 10.1080/01635581.2013.785005
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Topical Application of α-Tocopherol and/or N-Acetyl Cysteine on Argemone Oil/Alkaloid-Induced Skin Tumorigenesis in Mice

Abstract: Since bioantioxidants in plasma of Epidemic Dropsy patients [a condition caused by consumption of adulterated mustard oil with argemone oil (AO)] were found to be significantly decreased, the beneficial effect of N-acetyl cysteine (NAC) and α-tocopherol (TOCO) against AO- or sanguinarine (SANG)-induced tumorigenicity was undertaken in mice. Topical application of TOCO and NAC either alone or in combination showed significant protection against AO/TPA- and SANG/TPA-induced skin tumorigenicity. Histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…showed that α-tocopherol (vitamin E) suppressed the growth of murine B16 melanomas in-vitro and in-vivo 27 . It is interesting to note that dl-α-tocopherol stimulated HaCaT wound healing in-vitro and exerted protective properties against skin induced tumorigenesis in mice 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…showed that α-tocopherol (vitamin E) suppressed the growth of murine B16 melanomas in-vitro and in-vivo 27 . It is interesting to note that dl-α-tocopherol stimulated HaCaT wound healing in-vitro and exerted protective properties against skin induced tumorigenesis in mice 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae have been shown to be an important source of tocopherol, a fat-soluble phenolic compound with varying degrees of vitamin E antioxidant activity [ 378 , 379 ]. A previous in vitro study showed that tocopherol decreased cell proliferation and activation of MAPKs and NF-κB signaling induced by argemone oil in HaCaT cells [ 380 ]. γ-tocopherol has been shown to have the most important anti-inflammatory activity and it can reduce PGE2 levels in vitro [ 381 ] and in vivo [ 382 , 383 ].…”
Section: Inflammation and Skin Cancermentioning
confidence: 99%
“…Vitamin E is a powerful lipophilic antioxidant that can quench and scavenge reactive oxygen species (10). Tocopherol also has several other functions, including inhibition of protein kinase C (PKC) activity and suppression of tumor angiogenesis (12). Like previous epidemiological studies considering associations between micronutrients such as retinoids and cancer risk, the role of antioxidant level for BCC development was not consistent (13, 14).…”
Section: Introductionmentioning
confidence: 99%